Pre-Service Teachers’ Reflective Practice and their Teaching Practicum Beliefs - Arlon Ponce Cadiz (Universitas Lampung, 2021)
While learning assessment serves as feedback for teachers in maintaining or improving teaching practice, reflective practice play can be seen in how pre-service teachers plan, design, implement and evaluate their teaching approaches. Practicing reflection can help pre-service teachers starting to embrace the value and passion of teaching which manifests in their professional teaching practice. This study was conducted to determine the reflective practice of pre-service teachers and their teaching practicum experience. Involved in this study were 103 pre-service teachers from the government Teacher Education Institution. The study used self-developed survey questionnaires on pre-service reflective practice and beliefs about their teaching practicum. Results showed that there is a significant relationship between the reflective practice of pre-service teachers and their beliefs about teaching practicum. On the other hand, reflective practice as well as the beliefs of male and female pre-service teachers about their teaching practicum does not have a significant difference. Teacher educators should impart reflective practice as part of their teaching practicum. For further research, a wide scope of study may be conducted involving different Teacher Education Institutions in private and public Higher Education Institutions to verify the findings in this study.Keywords: pre-service teachers, reflective practice, teaching practicumDOI: http://dx.doi.org/10.23960/jiip.v3i2.22854